Morbimortality in adult patients with septic arthritis: a three-year hospital-based study. Issue 1 (December 2016) - Ferrand, Julien; El Samad, Youssef; Brunschweiler, Benoit; Grados, Franck; Dehamchia-Rehailia, Nassima; Séjourne, Alice; Schmit, Jean-Luc; Gabrion, Antoine; Fardellone, Patrice; Paccou, Julien
Abstract Background The objective of this ambispective study was to determine outcomes and associated factors for adult patients with confirmed septic arthritis (SA). Methods All adult patients admitted to Amiens University Hospital between November 2010 and December 2013 with confirmed SA were included in the study. Patients with prosthetic joint infections were excluded. A statistical analysis was performed in order to identify risk factors associated with a poor outcome (including mortality directly attributable to SA). Results A total of 109 patients (mean ± SD age: 60.1 ± 20.1; 74 male/35 females) were diagnosed with SA during the study period. The most commonly involved sites were the small joints (n = 34, 31.2 %) and the knee (n = 25, 22.9 %). The most frequent concomitant conditions were cardiovascular disease (n = 45, 41.3 %) and rheumatic disease (n = 39, 35.8 %). One hundred patients (91.7 %) had a positive microbiological culture test, with Staphylococcus aureus as the most commonly detected pathogen (n = 59, 54.1 %). Mortality directly attributable to SA was relatively infrequent (n = 6, 5.6 %) and occurred soon after the onset of SA (median [range]: 24 days [1–42]). Major risk factors associated with death directly attributable to SA were older age (p = 0.023), high C-reactive protein levels (p = 0.002), diabetes mellitus (p = 0.028), rheumatoid arthritis and other inflammatory rheumatic diseases (p = 0.021), confusion on admission (p = 0.012), bacteraemia (p = 0.015), a low creatinine clearance rate (p = 0.009) and the presence of leg ulcers/eschars (p = 0.003). The median duration of follow-up (in patients who survived for more than 6 months) was 17 months [6–43]. The proportion of poor functional outcomes was high (31.8 %). Major risk factors associated with a poor functional outcome were older age (0.049), hip joint involvement (p = 0.003), the presence of leg ulcers/eschars (p = 0.012), longer time to presentation (0.034) and a low creatinine clearance rate (p = 0.013). Conclusions In a university hospital setting, SA is still associated with high morbidity and mortality rates.